The Keynesians ( a letter from America to friend) - P. SYLOS LABINI (PSL Quarterly Review, 2014)
In the present article, the author gives impressions of the various and conflicting developments to which the theories of Keynes have led in the United States, and assumes a definitely critical position with regard to the “new economics”.